IEC 60909 and ANSI standards comparison with ASCC based fault calculations of Iraqi power system. Issue 1 (1st January 2019) - N. Lafta, Yasar; A. Shalash, Nadheer; N. Abd, Yaser; A. Al- Lami, Ali
Abstract: The calculation of short circuit (SC) current has to be accurate because of their importance in power protection system's design and to determine the capacity of the protective devices. Therefore, there are many standards and programs to estimate SC calculation. The aim of this paper is to provide further calculation methods' understanding for determining SC current in PSS/E program. Here, the characteristics of SC at the busbars of Al-Nassiriya power plant; with 400/132 KV local transformers; which is part of Iraqi power system is analyzed using PSS/E program methods such as automatic sequence fault calculation (ASCC), IEC 60909 and (ANSI) standards. The finding of results comparison between the three methods refers that IEC standard result was the most accurate one in subtransient current calculation. This paper concludes that IEC have the best method to be followed in subtransient current calculations for Iraq power grid expansion studies and planning.